PENINGKATAN PENGUASAAN KOSAKATA BAHASA INGGERIS MELALUI MODEL PEMBELAJARAN KOPERATIF. Suatu Penelitian Tindakan pada siswa kelas III SD Negeri 2 Baruga Kendari, Sulawesi Tenggara. - Yusniati Rambe (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2016)
This research is aimed at increasing the student's vocabulary mastery through cooperative learning approach. The subyects were the third grade at the second semester student of Elementary School 2 Baruga Kendari Southeast Sulawesi, academic year 20J3/2014.The data were collected through observation, pre test, post test and teaching-learning proccess. Based on the result of the pre test, an action program was designed.. The post test was a mean to evaluate the action conducted in one semester. The instrument of this action research were the researcher, collaborator, the training and the given test, were some aspect used to improved the student's vocabulary ability in English, namely: the aspect of understanding, pronounciation, and action The result of this research based on the value compared from pest test and post test, showing the increasing of vocabulary mastering about 30% at understanding, 30%pronounciation, and 70%action The action reseach was conducted in one semester consisting of ten sessions of each cycle. The research went through two cycles including twenty times of meeting or teaching and learning proses. Each cycles has its ownfocus of learning. The data analyzed were qualitative data. The improvement of vocabulary ability could be observed trough the teachingÂ learning procces and trough the result of the training as well as the tests.